RUMAH TAHFIDZ AL-QURAN DI KABUPATEN TABALONG - Rahmitha, Aulia; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Muslims' interest in studying the Koran is currently decreasing, this is proven by research results from the Al-Quran Science Institute in Indonesia in 2022 that 72.25% of Indonesian Muslims are illiterate in the Koran. One of the efforts to help Muslims study the Koran is by establishing the Al-Quran Tahfidz House. The Tahfidz Al-Quran House program is also the vision of Tabalong Regency, which is the location of the design object. The Tabalong Regional Government created the 100 Tahfidz Houses program in Tabalong Regency. The design problem is related to the peaceful aspect of the space and environment of the Tahfidz House. One method that can solve this problem is William Pena's Architectural Programming method which focuses on problem seeking to produce problem solving in the form of programmatic concepts and schematic designs. The design of the Tahfidz Al-Quran House takes the Mutmainnah concept, where the Mutmainnah concept focuses on the physical response of the building to the user's tranquility in the form of responses from sound aspects, building mass layout, lighting, materials, colors, aromas and shapes.